PENGARUH MOTIVASI DAN BIAYA PENDIDIKAN PADA MINAT MAHASISWA UNTUK MENGIKUTI PROGRAM STUDI MAGISTER AKUNTANSI - Dewa Ayu Ratih Purnama Sari; Ni Putu Ayu Kusumawati; Rai Dwi Andayani W (UNHI Press, 2022)
Accounting is one of the study programs that are in great demand by students in universities, especially the Faculty of Economics, this can be seen from the number of students who choose accounting study programs at both State Universities and Private Universities. The level of interest of accounting students in the accounting master's study program is determined by motivation and educational costs. Respondents in this study were final year students from 5 economic faculties in 5 universities in the Denpasar area. This research is an empirical research with a sampling technique using the Slovin formula. How the data aggregation in this research is by. Based on the results of the study, it shows that the variables of social motivation, career motivation, economic motivation, and education costs have a positive effect on student interest in joining the accounting master's program.).